Sodium-ion battery positive electrode material as well as preparation method and application thereof
By using a one-step precipitation method to prepare the precursor salt with a gradient structure in the sodium-ion battery cathode material, and mixing it with the sodium source and the inorganic acid ion source for calcination, a layered oxide cathode material coated with the solid electrolyte is formed, which solves the problem of nickel-based layered The problem of structural instability of oxide materials under high voltage has been achieved, and the effects of high capacity and long cycle life have been achieved.
Patent Information
- Application Number
- CN202411435981.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-15
AI Technical Summary
Nickel-based layered sodium oxide battery positive electrode materials are prone to structural instability, interface side reactions and metal ion dissolution under high voltage, resulting in irreversible capacity attenuation.
Through step -by -step preparation from core to surface NI elements, the content of the content of the content of the element of non -lively metal M elements gradually increases, and it is mixed with sodium source and inorganic acid root ion source to form Sodium ion batteries of solid electrolyte.
It achieves high capacity, long cycle life and excellent rate performance of the cathode material, reduces the interface side reaction between the electrolyte and the layered oxide, and promotes sodium ion diffusion.
Smart Images

Figure CN119340361A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a sodium ion battery positive electrode material and a preparation method and application thereof. Background Art
[0002] As electric vehicles continue to be popularized, the demand for lithium-ion batteries is also increasing. However, the reserves of lithium resources on the earth are very limited and unevenly distributed on the earth. Even considering the recycling of power lithium-ion batteries, the lithium resources available for mining cannot supply the increasing number of electric vehicles. Therefore, it is necessary to find alternatives to lithium-ion batteries to meet the needs of large-scale energy storage, and sodium-ion batteries have received widespread attention. The biggest advantage of sodium-ion batteries is their low cost and abundant reserves. The abundance of sodium in the earth's crust is 2.64%, ranking sixth among all elements, and the abundance of lithium is only 0.006%. Sodium-ion batteries mainly include positive electrode materials, electrolytes, diaphragms and negative electrode materials, among which the performance of the battery is mainly determined by the positive and negative electrode materials.
[0003] In recent years, the research on negative electrode materials and electrolytes has made great progress. Relatively speaking, the development of positive electrode materials is relatively slow, and the specific capacity of positive electrode materials is much smaller than that of negative electrode materials. Therefore, improving and enhancing the performance of positive electrode materials is critical to the development of sodium-ion batteries. The main positive electrode materials for sodium-ion batteries are: transition metal layered oxides, such as tunnel-type layered oxides with less sodium content, P2-type layered oxides with a sodium content of about 0.55-0.75, and O3-type layered oxides with a sodium content of more than 0.8; polyanion materials, such as phosphates, fluorophosphates, pyrophosphates, and sulfates; Prussian blue compounds, such as cyanides formed by the coordination of transition metals and Na; sodium-containing organic molecular polymers. Among them, P2 and O3-type transition metal layered oxides have the highest theoretical capacity, and the initial Na content of O3-type materials is higher than that of P2-type materials, and they usually have higher capacity.
[0004] Similar to ternary lithium-ion batteries, Ni 2+ / Ni 3+ / Ni 4+Redox pairs show the greatest potential in sodium battery systems. Therefore, among sodium ion positive electrode materials, nickel-based layered oxide sodium ion positive electrode materials theoretically have the characteristics of high voltage and high capacity. However, nickel-based layered oxides are prone to many adverse reactions and structural instability under high voltage, such as multiphase transitions in the voltage range of 2-4V, particle rupture caused by unit cell changes during charge and discharge, interface side reactions between electrodes and electrolytes, and transition metal dissolution, which cause the material to suffer serious irreversible capacity decay during charge and discharge. Through the core-shell structure, the core is a high-nickel material with electrochemical activity, and the shell is an inactive metal ion material that can maintain structural stability to meet the needs of high capacity and long cycle. However, this type of core-shell structured layered oxide positive electrode material is prone to grain boundaries and even gaps at the junction of the core and the shell, resulting in larger impedance and lower ionic conductivity, and the uniformity of the formed precursor primary ions is poor, which is not conducive to the overall performance of the positive electrode material. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a sodium ion battery positive electrode material and a preparation method and application thereof, wherein a precursor salt with a gradually decreasing Ni element content from the core to the surface and a gradually increasing inactive metal M element content is prepared by a one-step precipitation method, and then mixed and calcined with a sodium source and an inorganic acid radical ion source in steps or in one step to obtain a sodium ion battery positive electrode material with a solid electrolyte in situ coated on the surface of a layered oxide. The positive electrode material has a high content of active metal components in the core and a stable overall structure, and the surface solid electrolyte layer can reduce the interface side reaction between the electrolyte and the layered oxide, and promote the diffusion of sodium ions, so that the sodium ion battery constructed by it has high capacity, long cycle life and excellent rate performance.
[0006] Specifically, the following technical solutions are provided:
[0007] The first aspect of the present invention provides a sodium ion battery positive electrode material, comprising a layered oxide and a solid electrolyte layer coated on the surface of the layered oxide;
[0008] The chemical formula of the layered oxide is Na n Ni x M y O2, the Ni content of the layered oxide gradually decreases from the core to the surface, and the M content gradually increases;
[0009] The solid electrolyte layer comprises one or more of sodium phosphate, sodium silicate and sodium pyrophosphate, and the solid electrolyte layer comprises at least one element of the M element;
[0010] Wherein, M is selected from one or more of Ti, Co, Mn, Zn, Fe, Al and Cu;
[0011] 0.8≤n≤1.1, 0.4≤x≤0.75, x+y=1.
[0012] Further, the molar ratio of the layered oxide to the solid electrolyte in the solid electrolyte layer is preferably 1:(0.01-0.1);
[0013] Furthermore, the layered oxide Na n Ni x M y O2 is also doped with element A, and the element A is selected from one or more of Mo, W, Sb, Nb, Sn, Ca, Sr, Li, Y, V, Cr, La, Ti, Co, Mn, Mg, Zn, Fe, Al and Cu, and the element A and the element M are selected from different elements; the doping amount of element A in the layered oxide is not higher than 0.1.
[0014] The second aspect of the present invention provides a method for preparing the positive electrode material for a sodium ion battery according to the first aspect, comprising the following steps:
[0015] S1: providing a mixed solution A and a mixed solution B, wherein the mixed solution A and the mixed solution B are obtained by dissolving a Ni source and an M source in water; wherein,
[0016] The concentration of the Ni source in the mixed solution A is greater than the concentration of the Ni source in the mixed solution B;
[0017] The concentration of the M source in the mixed solution A is less than the concentration of the M source in the mixed solution B;
[0018] The metal element M in the M source is selected from one or more of Ti, Co, Mn, Mg, Zn, Fe, Al and Cu;
[0019] S2: continuously pumping the mixed solution B in S1 into the container containing the mixed solution A to form a precursor solution, and at the same time continuously pumping the precursor solution into a continuously stirred reaction container, and adding a precipitant and a complexing agent to react to obtain a precursor salt;
[0020] S3: uniformly mixing the precursor salt prepared in S2 with a sodium source, performing a first calcination treatment to obtain a layered oxide, heating and stirring the layered oxide and an inorganic acid radical ion source in the presence of a dispersant, separating and collecting the solid, performing a second calcination treatment, and obtaining the sodium ion battery positive electrode material; or,
[0021] The precursor salt prepared in S2 is heated and stirred with a sodium source and an inorganic acid radical ion source in the presence of a dispersant, and the solid is separated and collected for pre-calcination treatment, and then sintering treatment is performed to obtain the sodium ion battery positive electrode material.
[0022] Furthermore, in S1, the ratio of the total molar concentration of metal elements in the mixed solution A to the total molar concentration of metal elements in the mixed solution B is preferably 1:(0.65-1.05), and more preferably, the total molar concentration of metal elements in the mixed solution A is 1-10 mol / L.
[0023] Furthermore, in S1, the molar ratio of the Ni element to the M element in the mixed solution A is preferably 1:(0.02-1), and the molar ratio of the Ni element to the M element in the mixed solution B is preferably 1:(1.3-5).
[0024] Furthermore, in S1, the Ni source is selected from one or more of nickel carbonate, nickel sulfate, nickel acetate, nickel chloride, nickel nitrate and nickel phosphate; the M source is selected from one or more of carbonate, sulfate, acetate, chloride, nitrate and phosphate.
[0025] Furthermore, in S1, the mixed solution A and the mixed solution B further contain an A source; preferably, the A element in the A source is selected from one or more of Mo, W, Sb, Nb, Sn, Ca, Sr, Li, Y, V, Cr, La, Ti, Co, Mn, Mg, Zn, Fe, Al and Cu.
[0026] Further, in S1, the molar ratio of Ni element to A element in the mixed solution A is preferably 1:(0-0.4), and the molar ratio of Ni element to A element in the mixed solution B is preferably 1:(0-0.65); more preferably, the concentration of A element in the mixed solution A is greater than or equal to the concentration of A element in the mixed solution B.
[0027] Furthermore, in S2, the precipitant is selected from one or more of NaOH, NaHCO3, and Na2CO3.
[0028] Furthermore, in S2, the complexing agent is preferably NH3·H2O.
[0029] Furthermore, in S2, the continuous stirring rate is preferably 500-1000 rpm.
[0030] Furthermore, in S2, the pH of the reaction is preferably 9-12, the reaction temperature is preferably 50-90° C., and the reaction time is preferably 12-24 h.
[0031] Further, in S2, the reaction is carried out under a protective atmosphere, and the protective atmosphere includes but is not limited to nitrogen and / or argon.
[0032] Further, in S3, the ratio of the total molar amount of metal elements in the precursor salt to the molar amount of sodium element in the sodium source is preferably 1:(1-1.1); more preferably, the sodium source is selected from one or more of sodium carbonate, sodium acetate, sodium oxalate, and sodium nitrate.
[0033] Further, in S3, the molar ratio of the layered oxide to the inorganic acid ions in the inorganic acid ion source is preferably 1:(0.01-0.1); more preferably, the inorganic acid ion source is selected from one or more of a phosphoric acid source, a silicate source and a pyrophosphate source; the phosphoric acid source is selected from one or more of phosphoric acid, sodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, aluminum phosphate, zirconium phosphate, zirconium hydrogen phosphate, magnesium phosphate, yttrium phosphate, ammonium phosphate, ammonium dihydrogen phosphate, and magnesium ammonium phosphate; the silicate source is selected from one or more of silicic acid, sodium silicate, sodium metasilicate, sodium orthosilicate, and potassium silicate; and the pyrophosphate source is selected from one or more of pyrophosphate, sodium pyrophosphate, trisodium monohydrogen pyrophosphate, disodium dihydrogen pyrophosphate, and potassium pyrophosphate.
[0034] Furthermore, in S3, the dispersant is selected from one or more of ethanol, propanol, and N-methylpyrrolidone.
[0035] Furthermore, in S3, the temperature of the first calcination treatment is preferably 700-1000° C., and the time of the first calcination treatment is preferably 10-20 hours; and the first calcination treatment is performed in the presence of oxygen.
[0036] Furthermore, in S3, the temperature of the heating and stirring is preferably 50-90° C., the time of the heating and stirring is preferably 3-6 h, and the rate of the heating and stirring is preferably 200-800 rpm.
[0037] Furthermore, in S3, the temperature of the second calcination treatment is preferably 400-700° C., and the time of the second calcination treatment is preferably 5-10 h.
[0038] Furthermore, in S3, the temperature of the pre-sintering treatment is preferably 400-700°C, and the time of the pre-sintering treatment is preferably 3-6 hours; the temperature of the sintering treatment is preferably 700-1000°C, and the time of the sintering treatment is preferably 10-20 hours.
[0039] The third aspect of the present invention provides a positive electrode plate, comprising the sodium ion battery positive electrode material described in the first aspect or the sodium ion battery positive electrode material prepared by the preparation method described in the second aspect.
[0040] A fourth aspect of the present invention provides a sodium ion battery, comprising the positive electrode sheet described in the third aspect.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] 1. The present invention provides a sodium ion battery positive electrode material, comprising a layered oxide with a gradient distribution of metal elements and a solid electrolyte layer coated on the surface of the layered oxide. Among them, from the inside to the outside of the layered oxide, the Ni content gradually decreases, and the content of the relatively inactive metal M element gradually increases, so that the positive electrode material has a high capacity while reducing the strain on the particle surface, which is beneficial to inhibit surface cracks and electrolyte infiltration, reduce interface side reactions and metal ion dissolution; at the same time, the NASICON type solid electrolyte coating layer coated on the surface of the layered oxide can inhibit the interface side reaction with the electrolyte, reduce the dissolution of metal ions, and as a fast ion conductor, it can also promote Na + Diffusion is beneficial to improving capacity and rate performance.
[0043] 2. The present invention also provides a method for preparing the above-mentioned sodium ion battery positive electrode material, firstly preparing a precursor salt with a gradually decreasing Ni element content from the core to the surface and a gradually increasing inactive metal M element content by a one-step precipitation method, and then mixing and calcining with a sodium source and an inorganic acid radical ion source in steps or in one step to obtain a sodium ion battery positive electrode material with a solid electrolyte in situ coated on the surface of the layered oxide. The precursor salt powder prepared by the above-mentioned one-step precipitation method has good structural uniformity of primary particles, no obvious interface from the inside to the outside, and is not prone to phase separation between layers with different distribution contents of metal elements, and has good structural stability. However, it was found during the experiment that the high content of M element on the surface of the precursor salt could not completely react with the sodium source to form a layered oxide and enter the positive electrode material unit cell, but formed nano-sized particles of M oxide on the particle surface, which hindered the diffusion of sodium ions and reduced the ionic conductivity and capacity; based on this, the present invention can react with the residual sodium and M oxide on the surface of the layered oxide to form a NASICON-type solid electrolyte by introducing an inorganic acid radical ion source, which can effectively reduce impedance and gas production, increase capacity, and no need to synthesize or purchase NASICON-type solid electrolyte materials to coat the layered oxide to improve ionic conductivity, thereby effectively reducing the preparation cost. The above preparation method is simple to operate, has good process controllability, and the prepared sodium ion battery positive electrode material has excellent performance and is suitable for mass production.
[0044] 3. The sodium ion battery constructed using the above-mentioned sodium ion battery positive electrode material has high capacity, long cycle life and excellent rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a SEM image of the layered oxide before coating prepared in Example 1;
[0046] Figure 2 This is a SEM image of the coated positive electrode material prepared in Example 1;
[0047] Figure 3XRD superposition of the layered oxide and the positive electrode material prepared in Example 1;
[0048] Figure 4 This is a SEM image of the layered oxide before coating prepared in Example 6;
[0049] Figure 5 This is a SEM image of the coated positive electrode material prepared in Example 6;
[0050] Figure 6 This is the XRD overlay of the layered oxide and positive electrode material prepared in Example 6. DETAILED DESCRIPTION
[0051] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are for the purpose of describing specific embodiments only and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items. The term "includes" or "comprising" described in the present invention means that it may include or contain other components in addition to the components described. The term "includes" or "comprising" described in the present invention may also be replaced by the closed form "for" or "consisting of..."
[0052] As described in the background technology, nickel-based layered oxide sodium ion battery positive electrode materials are prone to many adverse reactions and structural instability under high voltage, such as multiphase transitions in the voltage range of 2-4V, particle rupture caused by changes in the unit cell during charge and discharge, interface side reactions between the electrode and the electrolyte, and transition metal dissolution, etc., resulting in the material suffering from severe irreversible capacity decay during charge and discharge. Through the core-shell structure, the core is a high-nickel material with electrochemical activity, and the shell is an inactive metal ion material that can maintain structural stability to meet the needs of high capacity and long cycle. However, this type of core-shell structured layered oxide positive electrode material is prone to grain boundaries and even gaps at the junction of the core and the shell, resulting in larger impedance and lower ionic conductivity, and the formed precursor primary ions have poor uniformity, which is not conducive to the overall performance of the positive electrode material.
[0053] To solve the above problems, the embodiments of the present invention provide a sodium ion battery positive electrode material, comprising a layered oxide and a solid electrolyte layer coated on the surface of the layered oxide; wherein:
[0054] The chemical formula of the layered oxide is Na n Ni x M y O2, the Ni content of the layered oxide gradually decreases from the core to the surface, and the M content gradually increases;
[0055] The solid electrolyte layer comprises one or more of sodium phosphate, sodium silicate and sodium pyrophosphate, and the solid electrolyte layer comprises at least one element of the M element;
[0056] Wherein, M is selected from one or more of Ti, Co, Mn, Zn, Fe, Al and Cu;
[0057] 0.8≤n≤1.1, 0.4≤x≤0.75, x+y=1.
[0058] In the present invention, the M element contained in the solid electrolyte layer is derived from residual M oxide of the layered oxide. Preferably, the solid electrolyte is obtained by the reaction of an inorganic acid radical ion source with residual sodium and M oxide on the surface of the layered oxide.
[0059] In the present invention, the molar ratio of the layered oxide to the solid electrolyte in the above-mentioned sodium ion battery positive electrode material is preferably 1:(0.01-0.1), for example 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.1, etc., including but not limited to the molar ratios listed above.
[0060] In the present invention, the layered oxide Na n Ni x M y O2 is also doped with element A, wherein element A can be selected from one or more of Mo, W, Sb, Nb, Sn, Ca, Sr, Li, Y, V, Cr, La, Ti, Co, Mn, Mg, Zn, Fe, Al and Cu, and element A and element M are selected from different elements; preferably, the doping amount of element A in the layered oxide is not higher than 0.1.
[0061] The present invention also provides a method for preparing the above-mentioned sodium ion battery positive electrode material, comprising the following steps:
[0062] S1: providing a mixed solution A and a mixed solution B, wherein the mixed solution A and the mixed solution B are obtained by dissolving a Ni source and an M source in water; wherein,
[0063] The concentration of the Ni source in the mixed solution A is greater than the concentration of the Ni source in the mixed solution B;
[0064] The concentration of the M source in the mixed solution A is less than the concentration of the M source in the mixed solution B;
[0065] The metal element M in the M source is selected from one or more of Ti, Co, Mn, Mg, Zn, Fe, Al and Cu;
[0066] S2: continuously pumping the mixed solution B in S1 into the container containing the mixed solution A to form a precursor solution, and at the same time continuously pumping the precursor solution into a continuously stirred reaction container, and adding a precipitant and a complexing agent to react to obtain a precursor salt;
[0067] S3: uniformly mixing the precursor salt prepared in S2 with a sodium source, performing a first calcination treatment to obtain a layered oxide, heating and stirring the layered oxide and an inorganic acid radical ion source in the presence of a dispersant, separating and collecting the solid, performing a second calcination treatment, and obtaining the sodium ion battery positive electrode material; or,
[0068] The precursor salt prepared in S2 is heated and stirred with a sodium source and an inorganic acid radical ion source in the presence of a dispersant, and the solid is separated and collected for pre-calcination treatment, and then sintering treatment is performed to obtain the sodium ion battery positive electrode material.
[0069] Different from the nickel-based layered oxide material with a core-shell structure in the prior art, for example, by first preparing a core precursor precipitate, and then dispersing the core precursor in a shell precursor metal solution, and finally forming a nickel-based layered oxide material with a negative core and a poor shell nickel, this type of core-shell structured layered oxide positive electrode material is prone to grain boundaries and even gaps at the junction of the core and the shell, resulting in a larger impedance and a lower ionic conductivity, and the primary ions of the formed precursor have poor uniformity, which is not conducive to the overall performance of the positive electrode material. The present invention prepares a precursor salt powder with a gradually decreasing Ni element content from the core to the surface and a gradually increasing inactive metal M element content by a one-step precipitation method, and the structural uniformity of the primary particles is good, there is no obvious interface from the inside to the outside, it is not easy to have phase separation between layers with different distribution contents of metal elements, the structural stability is good, and it is beneficial to reduce impedance and improve ionic conductivity. More importantly, the inventors found in the experimental process that residual sodium and impurity oxides (such as M oxides) exist on the surface of the layered oxide prepared by the above method. This is because the high content of M elements on the surface of the precursor salt cannot completely react with the sodium source to form layered oxides and enter the positive electrode material unit cell, but form nano-particles of M oxides on the particle surface. The presence of such impurity oxides will hinder the diffusion of sodium ions and reduce ionic conductivity and capacity. The present invention can react with residual sodium and M oxides on the surface of the layered oxide to form a NASICON-type solid electrolyte by introducing an inorganic acid radical ion source. On the one hand, it can effectively reduce impedance and gas production, increase capacity, and there is no need to synthesize or purchase NASICON-type solid electrolyte materials to coat the layered oxide to improve ionic conductivity, thereby effectively reducing preparation costs.
[0070] In the present invention, in S1, the ratio of the total molar concentration of metal elements in the mixed solution A to the total molar concentration of metal elements in the mixed solution B is preferably 1:(0.65-1.05), for example, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.05, etc.; more preferably, the total molar concentration of metal elements in the mixed solution A is 1-10 mol / L, for example, 2 mol / L, 4 mol / L, 6 mol / L, 8 mol / L, etc., including but not limited to the molar concentrations listed above.
[0071] In the present invention, in S1, the molar ratio of Ni element to M element in the mixed solution A is preferably 1:(0.02-1), for example, 1:0.1, 1:0.2, 1:0.25, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, etc., and the molar ratio of Ni element to M element in the mixed solution B is preferably 1:(1.3-5), for example, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, etc.; preferably, the Ni source can be selected from one or more of nickel carbonate, nickel sulfate, nickel acetate, nickel chloride, nickel nitrate and nickel phosphate; the M source can be selected from one or more of carbonate, sulfate, acetate, chloride, nitrate and phosphate.
[0072] In the present invention, in S1, mixed solution A and mixed solution B further contain A source; preferably, element A in source A is selected from one or more of Mo, W, Sb, Nb, Sn, Ca, Sr, Li, Y, V, Cr, La, Ti, Co, Mn, Mg, Zn, Fe, Al and Cu; more preferably, the molar ratio of Ni element to element A in mixed solution A is 1:(0-0.4), and the molar ratio of Ni element to element A in mixed solution B is 1:(0-0.65); in some preferred embodiments, the concentration of element A in mixed solution A is greater than or equal to the concentration of element A in mixed solution B.
[0073] In the present invention, in S2, the precipitant can be selected from one or more of NaOH, NaHCO3, and Na2CO3, and the complexing agent is preferably NH3·H2O.
[0074] In the present invention, in S2, the precursor solution is continuously pumped into the continuously stirred reaction vessel to make the solution in the reaction vessel more uniform, thereby obtaining a precursor salt with uniform structure; preferably, the continuous stirring rate is 500-1000 rpm.
[0075] In the present invention, in S2, the pH of the reaction system is controlled to be in the range of 9-12, the reaction temperature is preferably 50-90°C, and the reaction time is preferably 12-24h; the nickel content of the precursor solution continuously pumped into the reaction vessel gradually decreases and the M content gradually increases, and by controlling the pH, temperature and stirring speed of the reaction system, initial precipitation is performed to form crystals with a high nickel content, and then the nickel content gradually decreases and the M content gradually increases during the outward growth process, thereby forming a precursor salt with a gradually decreasing nickel content and a gradually increasing M content from the inside to the outside; preferably, the reaction is carried out under a protective atmosphere, and the protective atmosphere here includes but is not limited to nitrogen and / or argon.
[0076] In the present invention, in S3, the ratio of the total molar amount of metal elements in the precursor salt to the molar amount of sodium element in the sodium source is preferably 1:(1-1.1), for example, 1.05; wherein the sodium source can be selected from one or more of sodium carbonate, sodium acetate, sodium oxalate, and sodium nitrate.
[0077] In the present invention, in S3, the molar ratio of the layered oxide to the inorganic acid ion in the inorganic acid ion source is preferably 1:(0.01-0.1), for example, 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.1, etc., including but not limited to the molar ratios listed above; more preferably, the inorganic acid ion source can be selected from a phosphoric acid source, a silicate source and one or more of a pyrophosphate source; wherein the phosphate source is selected from one or more of phosphoric acid, sodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, aluminum phosphate, zirconium phosphate, zirconium hydrogen phosphate, magnesium phosphate, yttrium phosphate, ammonium phosphate, ammonium dihydrogen phosphate, and magnesium ammonium phosphate; the silicate source is selected from one or more of silicic acid, sodium silicate, sodium metasilicate, sodium orthosilicate, and potassium silicate; the pyrophosphate source is selected from one or more of pyrophosphate, sodium pyrophosphate, trisodium monohydrogen pyrophosphate, disodium dihydrogen pyrophosphate, and potassium pyrophosphate.
[0078] In the present invention, in S3, the dispersant is selected from one or more of ethanol, propanol, and N-methylpyrrolidone. The dispersant allows the layered oxide to be mixed more evenly with the inorganic acid ion source, thereby forming a uniform solid electrolyte coating layer on the surface of the layered oxide.
[0079] In the present invention, in S3, the temperature of the first calcination treatment is preferably 700-1000°C, such as 700°C, 800°C, 900°C, 1000°C, etc., and the time of the first calcination treatment is preferably 10-20h, such as 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, etc., including but not limited to the times listed above; wherein the first calcination treatment is carried out in the presence of oxygen, the precursor salt and the sodium source are subjected to the first calcination treatment in the presence of oxygen to form a layered oxide with an element gradient distribution structure, and then heated and stirred with an inorganic acid radical ion source to react the inorganic acid radical ion source with the residual sodium and M oxide on the surface of the layered oxide, and then a second calcination treatment is performed on the surface of the layered oxide. To form a solid electrolyte coating layer, preferably, the heating and stirring temperature is 50-90°C, for example, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, etc., the heating and stirring time is preferably 3-6h, for example, 4h or 5h, etc., the heating and stirring rate is preferably 200-800rpm, for example, 200rpm, 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 800rpm, etc., the temperature of the second calcination treatment is preferably 400-700°C, for example, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, etc., and the time of the second calcination treatment is 5-10h, for example, 5h, 6h, 7h, 8h, 9h, 10h, etc.
[0080] In the present invention, in S3, the precursor salt can also be directly mixed with the sodium source and the inorganic acid radical ion source to prepare the sodium ion battery positive electrode material by pre-sintering and sintering, wherein the pre-sintering temperature is preferably 400-700°C, for example, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, etc., and the pre-sintering time is preferably 3-6h, for example, 3h, 4h, 5h, 6h, etc.; the sintering temperature is preferably 700-1000°C, for example, 700°C, 800°C, 900°C, 1000°C, etc., and the sintering time is preferably 10-20h, for example, 10h, 12h, 14h, 16h, 18h, 20h, etc., including but not limited to the temperatures or times listed above.
[0081] The embodiments of the present invention also provide a positive electrode sheet, which includes the positive electrode material for a sodium ion battery prepared by the above preparation method.
[0082] In addition, the embodiments of the present invention also provide a sodium ion battery, including the above-mentioned positive electrode plate, which exhibits high capacity, long cycle life and excellent rate performance.
[0083] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0084] Example 1
[0085] This embodiment relates to the preparation of a positive electrode material for a sodium ion battery, and the specific operations are as follows:
[0086] (1) Preparation of mixed solution A: Nickel sulfate, manganese sulfate and titanium chloride were weighed in a molar ratio of Ni:Mn:Ti=8:1:1, and dissolved in deionized water to prepare a mixed solution A with a molar concentration of 4 mol / L;
[0087] Preparation of mixed solution B: weigh the corresponding nickel sulfate, manganese sulfate and titanium chloride in a molar ratio of Ni:Mn:Ti=2:3:5, dissolve them in deionized water to prepare a mixed solution B with a molar concentration of 4.2 mol / L;
[0088] (2) The mixed solution B prepared in step (1) was continuously pumped into the container containing the mixed solution A to form a precursor solution. At the same time, the precursor solution was continuously pumped into a 5L reactor that was continuously stirred, and 4 mol / L NaOH and 2 mol / L NH3·H2O were pumped into the reactor. During the reaction, the pH value was controlled to be about 11. The reaction was carried out at a temperature of 90°C and a stirring speed of 1000 rpm for 24 hours, and then aged, filtered, washed, and dried to obtain a precursor powder Ni 0.5 Mn 0.2 Ti 0.3 (OH)2.
[0089] (3) The precursor powder prepared in step (2) and sodium carbonate were weighed and mixed evenly according to a molar ratio of (Ni+Mn+Ti):Na=1:1.05, sintered at 900°C for 12 h in an air atmosphere in a muffle furnace, and pulverized after cooling to obtain a layered oxide powder NaNi 0.5 Mn 0.2 Ti 0.3 O2.
[0090] (4) The layered oxide powder NaNi prepared in step (3) 0.5 Mn 0.2 Ti 0.3 O2 and diammonium phosphate according to the molar ratio of NaNi 0.5 Mn 0.2 Ti 0.3 O2:PO4 3-=1:0.03 weighed and mixed evenly in ethanol, heated and stirred at 90°C in an oil bath, filtered, washed, dried after the reaction was complete, sintered at 500°C in an air atmosphere in a muffle furnace for 6h, sieved after cooling, and obtained the positive electrode material 0.01(NaTi2(PO4)3)@NaNi 0.5 Mn 0.2 Ti 0.3 O2.
[0091] The layered oxide powder NaNi prepared in this example 0.5 Mn 0.2 Ti 0.3 O2 and positive electrode material 0.03(Na 3- 4x Ti x PO4)@NaNi 0.5 Mn 0.2 Ti 0.3 The SEM images of O2 are shown in Figure 1 , 2 As shown by Figure 1 , 2 It can be seen that a large number of small particles adhere to the surface of the layered oxide particles prepared in this embodiment, and the surface of the positive electrode material particles prepared by post-treatment with ammonium dihydrogen phosphate is clean ( Figure 2 It is speculated that the small particles on the surface of the layered oxide react with ammonium dihydrogen phosphate to form a solid electrolyte coated on the surface of the layered oxide.
[0092] The layered oxide NaNi prepared in this example 0.5 Mn 0.2 Ti 0.3 O2 and positive electrode material 0.01(NaTi2(PO4)3)@NaNi 0.5 Mn 0.2 Ti 0.3 The XRD pattern of O2 is as follows Figure 3 As shown, it is consistent with the R-3m structure, both of which are O3-type positive electrode materials. 0.5 Mn 0.2 Ti 0.3 O2 can be observed at diffraction peaks of 25° and 47° belonging to the TiO2 phase, while this impurity phase is not found in the XRD diagram of the positive electrode material prepared by post-treatment with ammonium dihydrogen phosphate, further indicating that the introduction of ammonium dihydrogen phosphate can fully react with TiO2 to form a thin coating layer on the surface of the particles.
[0093] Example 2
[0094] This embodiment relates to the preparation of a positive electrode material for a sodium ion battery, and the specific operations are as follows:
[0095] (1) Preparation of mixed solution A: Nickel sulfate, cobalt sulfate and manganese sulfate were weighed in a molar ratio of Ni:Co:Mn=8:1:1, and dissolved in deionized water to prepare a mixed solution A with a molar concentration of 4 mol / L;
[0096] Preparation of mixed solution B: weigh the corresponding nickel sulfate, cobalt sulfate and manganese sulfate in a molar ratio of Ni:Co:Mn=2:3:5, dissolve them in deionized water to prepare a mixed solution B with a molar concentration of 4.2 mol / L;
[0097] (2) The mixed solution B prepared in step (1) was continuously pumped into the container containing the mixed solution A to form a precursor solution. At the same time, the precursor solution was continuously pumped into a 5L reactor that was continuously stirred, and 4 mol / L NaOH and 2 mol / L NH3·H2O were pumped into the reactor. During the reaction, the pH value was controlled to be about 11. The reaction was carried out at a temperature of 90°C and a stirring speed of 1000 rpm for 24 hours, and then aged, filtered, washed, and dried to obtain a precursor powder Ni 0.5 Co 0.2 Mn 0.3 (OH)2.
[0098] (3) The precursor powder prepared in step (2) is mixed with sodium carbonate, sodium silicate, and ammonium dihydrogen phosphate in a molar ratio of (Ni+Co+Mn):Na:SiO4 4- :PO4 3- =1:1.05:0.02:0.01 weighed and mixed evenly in ethanol, heated and stirred at 90°C in an oil bath, filtered, washed and dried after the reaction was complete, pre-sintered at 500°C in an air atmosphere in a muffle furnace for 6h, then heated to 900°C and sintered for 12h, sieved after cooling, and obtained the positive electrode material 0.02(Na2MnSiO4)·0.01(Na 0.33 Mn 0.67 PO4)@NaNi 0.5 Co 0.2 Mn 0.3 O2.
[0099] Example 3
[0100] This embodiment relates to the preparation of a positive electrode material for a sodium ion battery, and the specific operations are as follows:
[0101] (1) Preparation of mixed solution A: Weigh the corresponding nickel sulfate, zinc sulfate and manganese sulfate in a molar ratio of Ni:Zn:Mn=8:1:1, and dissolve them in deionized water to prepare a mixed solution A with a molar concentration of 4 mol / L;
[0102] Preparation of mixed solution B: Weigh the corresponding nickel sulfate, zinc sulfate and manganese sulfate in a molar ratio of Ni:Zn:Mn=2:3:5, dissolve them in deionized water to prepare a mixed solution B with a molar concentration of 4.2 mol / L;
[0103] (2) The mixed solution B prepared in step (1) was continuously pumped into the container containing the mixed solution A to form a precursor solution. At the same time, the precursor solution was continuously pumped into a 5L reactor that was continuously stirred, and 4 mol / L NaOH and 2 mol / L NH3·H2O were pumped into the reactor. During the reaction, the pH value was controlled to be about 11. The reaction was carried out at a temperature of 90°C and a stirring speed of 1000 rpm for 24 hours, and then aged, filtered, washed, and dried to obtain a precursor powder Ni 0.5 Zn 0.2 Mn 0.3 (OH)2.
[0104] (3) The precursor powder prepared in step (2) is mixed with sodium carbonate, sodium silicate, and ammonium dihydrogen phosphate in a molar ratio of (Ni+Zn+Mn):Na:SiO4 4- :PO4 3- =1:1.05:0.02:0.01 weighed and mixed evenly in ethanol, heated and stirred at 90°C in an oil bath, filtered, washed and dried after the reaction was complete, pre-sintered at 500°C in an air atmosphere in a muffle furnace for 6h, then heated to 900°C and sintered for 12h, sieved after cooling, and obtained the positive electrode material 0.02(Na2MnSiO4)·0.01(Na 0.33 Mn 0.67 PO4)@NaNi 0.5 Zn 0.2 Mn 0.3 O2.
[0105] Example 4
[0106] This embodiment relates to the preparation of a positive electrode material for a sodium ion battery, and the specific operations are as follows:
[0107] (1) Preparation of mixed solution A: Nickel sulfate, copper sulfate and manganese sulfate were weighed in a molar ratio of Ni:Cu:Mn=8:1:1, and dissolved in deionized water to prepare a mixed solution A with a molar concentration of 4 mol / L;
[0108] Preparation of mixed solution B: Weigh the corresponding nickel sulfate, copper sulfate and manganese sulfate in a molar ratio of Ni:Cu:Mn=2:3:5, dissolve them in deionized water to prepare a mixed solution B with a molar concentration of 4.2 mol / L;
[0109] (2) The mixed solution B prepared in step (1) was continuously pumped into the container containing the mixed solution A to form a precursor solution. At the same time, the precursor solution was continuously pumped into a 5L reactor that was continuously stirred, and 4 mol / L NaOH and 2 mol / L NH3·H2O were pumped into the reactor. During the reaction, the pH value was controlled to be about 11. The reaction was carried out at a temperature of 90°C and a stirring speed of 1000 rpm for 24 hours, and then aged, filtered, washed, and dried to obtain a precursor powder Ni 0.5 Cu 0.2 Mn 0.3 (OH)2.
[0110] (3) The precursor powder prepared in step (2) is mixed with sodium carbonate, sodium silicate, and ammonium dihydrogen phosphate in a molar ratio of (Ni+Cu+Mn):Na:SiO4 4- :PO4 3- =1:1.05:0.02:0.01 weighed and mixed evenly in ethanol, heated and stirred at 90°C in an oil bath, filtered, washed and dried after the reaction was complete, pre-sintered at 500°C in an air atmosphere in a muffle furnace for 6h, then heated to 900°C and sintered for 12h, sieved after cooling, and obtained the positive electrode material 0.02(Na2MnSiO4)·0.01(Na 0.33 Mn 0.67 PO4)@NaNi 0.5 Cu 0.2 Mn 0.3 O2.
[0111] Example 5
[0112] This embodiment relates to the preparation of a positive electrode material for a sodium ion battery, and the specific operations are as follows:
[0113] (1) Preparation of mixed solution A: Nickel sulfate, iron sulfate and manganese sulfate were weighed in a molar ratio of Ni:Fe:Mn=4:1:1, respectively, and dissolved in deionized water to prepare a mixed solution A with a molar concentration of 4 mol / L;
[0114] Preparation of mixed solution B: Weigh the corresponding nickel sulfate and manganese sulfate in a molar ratio of Ni:Mn=1:3, dissolve them in deionized water to prepare a mixed solution B with a molar concentration of 4.2 mol / L;
[0115] (2) The mixed solution B prepared in step (1) was continuously pumped into the container containing the mixed solution A to form a precursor solution. At the same time, the precursor solution was continuously pumped into a 5L reactor that was continuously stirred, and 4 mol / L NaOH and 2 mol / L NH3·H2O were pumped into the reactor. During the reaction, the pH value was controlled to be about 11. The reaction was carried out at a temperature of 90°C and a stirring speed of 1000 rpm for 24 hours, and then aged, filtered, washed, and dried to obtain a precursor powder Ni 0.5 Fe 0.1 Mn 0.4 (OH)2.
[0116] (3) The precursor powder prepared in step (2) and sodium carbonate were weighed and mixed evenly according to a molar ratio of (Ni+Fe+Mn):Na=1:1.05, sintered at 900°C for 12 h in an air atmosphere in a muffle furnace, and pulverized after cooling to obtain a layered oxide powder NaNi 0.5 Fe 0.1 Mn 0.4 O2.
[0117] (4) The layered oxide powder NaNi prepared in step (3) 0.5 Fe 0.1 Mn 0.4 O2 and aluminum phosphate according to the molar ratio of NaNi 0.5 Fe 0.1 Mn 0.4 O2:PO4 3- =1:0.03 weighed and mixed evenly in ethanol, heated and stirred at 90°C in an oil bath, filtered, washed and dried after the reaction was complete, sintered at 500°C in an air atmosphere in a muffle furnace for 6h, sieved after cooling, and obtained the positive electrode material 0.01(Na2AlMn(PO4)3)@NaNi 0.5 Fe 0.1 Mn 0.4 O2.
[0118] Example 6
[0119] This embodiment relates to the preparation of a positive electrode material for a sodium ion battery, and the specific operations are as follows:
[0120] (1) Preparation of mixed solution A: Weigh the corresponding nickel sulfate and manganese sulfate in a molar ratio of Ni:Mn=4:1, dissolve them in deionized water to prepare a mixed solution A with a molar concentration of 4 mol / L;
[0121] Preparation of mixed solution B: Weigh the corresponding nickel sulfate and manganese sulfate at a molar ratio of Ni:Mn=1:4, dissolve them in deionized water to prepare a mixed solution B with a molar concentration of 4.2 mol / L;
[0122] (2) The mixed solution B prepared in step (1) was continuously pumped into the container containing the mixed solution A to form a precursor solution. At the same time, the precursor solution was continuously pumped into a 5L reactor that was continuously stirred, and 4 mol / L NaOH and 2 mol / L NH3·H2O were pumped into the reactor. During the reaction, the pH value was controlled to be about 11. The reaction was carried out at a temperature of 90°C and a stirring speed of 1000 rpm for 24 hours, and then aged, filtered, washed, and dried to obtain a precursor powder Ni 0.5 Mn 0.5 (OH)2.
[0123] (3) The precursor powder prepared in step (2) and sodium carbonate were weighed and mixed evenly according to a molar ratio of (Ni+Mn):Na=1:1.05, sintered at 900°C for 12 h in an air atmosphere in a muffle furnace, and pulverized after cooling to obtain a layered oxide powder NaNi 0.5 Mn 0.5 O2.
[0124] (4) The layered oxide powder NaNi prepared in step (3) 0.5 Mn 0.5 O2 and disodium dihydrogen pyrophosphate according to the molar ratio of NaNi 0.5 Mn 0.5 O2:P2O7 4- =1:0.03 weighed and mixed evenly, sintered at 500 °C for 6 h in a muffle furnace under air atmosphere, and sieved after cooling to obtain the positive electrode material 0.01(Na4Mn(P2O7)2)@NaNi 0.5 Mn 0.5 O2.
[0125] Cathode MaterialNaNi 0.5 Mn 0.5 O2 and 0.01(Na4Mn(P2O7)2)@NaNi 0.5 Mn 0.5 The SEM images of O2 are shown in Figure 4 , 5 As shown, Figure 4 There are small particles attached to the surface of the particles. Figure 5 The particle surface is relatively clean. Positive electrode material NaNi 0.5 Mn 0.5 O2 and 0.01(Na4Mn(P2O7)2)@NaNi 0.5 Mn 0.5 The XRD pattern of O2 is as follows Figure 6 As shown, it is consistent with the R-3m structure and is an O3-type positive electrode material, but the former has impurity peaks at 35° and 42°, corresponding to the MnO phase, while the latter has no impurity phase, indicating that MnO reacts fully with disodium dihydrogen pyrophosphate to form a thin coating layer on the surface of the particles.
[0126] Comparative Example 1
[0127] This comparative example relates to the preparation of a positive electrode material for a sodium ion battery, and the only difference from Example 1 is that the metal elements in the layered oxide are evenly distributed without a gradient structure; the specific operation is as follows:
[0128] (1) Preparation of precursor solution: Nickel sulfate, manganese sulfate and titanium chloride were weighed in a molar ratio of Ni:Mn:Ti=5:2:3 and dissolved in deionized water to prepare a precursor solution with a molar concentration of 4 mol / L.
[0129] (2) The precursor solution prepared in step (1) was pumped into a 5L reactor with continuous stirring, and 4 mol / L NaOH and 2 mol / L NH3·H2O were pumped into the reactor. During the reaction, the pH value was controlled to be about 11. The reaction was carried out at a temperature of 90°C and a stirring speed of 1000 rpm for 24 hours, and then aged, filtered, washed, and dried to obtain a precursor powder N i0.5 Mn 0.2 Ti 0.3 (OH)2.
[0130] Steps (3) and (4) are consistent with Example 1 to prepare the positive electrode material 0.03(Na3PO4)@NaNi 0.5 Mn 0.2 Ti 0.3 O2.
[0131] Comparative Example 2
[0132] This comparative example relates to the preparation of a positive electrode material for a sodium ion battery, and the only difference from Example 1 is that before adding the inorganic acid ion source, the layered oxide is surface treated with oxalic acid. The specific operation is as follows:
[0133] Steps (1) to (3) are consistent with those in Example 1;
[0134] (4) The layered oxide powder NaNi prepared in step (3) 0.5 Mn 0.2 Ti 0.3 O2 is added to a 0.1 mol / L oxalic acid ethanol solution, heated and stirred at 60°C in an oil bath, and filtered and washed after the reaction is complete to remove the M2 oxide and residual sodium on the surface of the layered oxide powder. The molar ratio is NaNi 0.5 Mn 0.2 Ti 0.3O2:PO4=1:0.03 Weigh sodium phosphate, add layered oxide powder and sodium phosphate into ethanol, heat and stir at 90℃ in an oil bath, filter, wash and dry after the reaction is complete, sinter at 500℃ in an air atmosphere in a muffle furnace for 6h, and sieve after cooling to obtain the finished cathode material 0.03(Na3PO4)@NaNi 0.5 Mn 0.2 Ti 0.3 O2.
[0135] Comparative Example 3
[0136] This comparative example relates to the preparation of a positive electrode material for a sodium ion battery, and the only difference from Example 1 is that in step (4), a solid electrolyte layer is coated on the surface of the layered oxide by adding ammonium dihydrogen phosphate and titanium chloride; the specific operation is as follows:
[0137] Steps (1) to (3) are consistent with those in Example 1;
[0138] (4) The layered oxide powder NaNi prepared in step (3) 0.5 Mn 0.2 Ti 0.3 O2 and diammonium phosphate, titanium chloride according to the molar ratio of NaNi 0.5 Mn 0.2 Ti 0.3 O2:PO4 3- :Ti=1:0.03:0.02 were weighed and mixed evenly in ethanol, heated and stirred at 90℃ in an oil bath, filtered, washed and dried after the reaction was complete, sintered at 500℃ in an air atmosphere in a muffle furnace for 6h, sieved after cooling, and obtained the positive electrode material 0.01(NaTi2(PO4)3)@NaNi 0.5 Mn 0.2 Ti 0.3 O2.
[0139] Comparative Example 4
[0140] This comparative example relates to the preparation of a positive electrode material for a sodium ion battery, and the only difference from Example 6 is that the metal elements in the layered oxide are evenly distributed without a gradient structure; the specific operation is as follows:
[0141] (1) Preparation of precursor solution: Nickel sulfate and manganese sulfate were weighed in a molar ratio of Ni:Mn=1:1 and dissolved in deionized water to prepare a precursor solution with a molar concentration of 4 mol / L.
[0142] (2) The precursor solution prepared in step (1) was pumped into a 5L reactor with continuous stirring, and 4mol / L NaOH and 2mol / L NH3·H2O were pumped into the reactor. During the reaction, the pH value was controlled to be about 11. The reaction was carried out at a temperature of 90°C and a stirring speed of 1000 rpm for 24 hours, and then aged, filtered, washed, and dried to obtain a precursor powder Ni 0.5 Mn 0.5 (OH)2.
[0143] Step (3) is consistent with Example 4 to prepare the positive electrode material 0.01(Na4P2O7)@NaNi 0.5 Mn 0.5 O2.
[0144] Comparative Example 5
[0145] This comparative example relates to the preparation of a positive electrode material for a sodium ion battery, and the only difference from Example 6 is that before adding the inorganic acid ion source, the layered oxide is surface treated with oxalic acid. The specific operation is as follows:
[0146] Steps (1)-(3) are consistent with Example 4;
[0147] (4) The layered oxide powder NaNi prepared in step (3) 0.5 Mn 0.5 O2 is added to a 0.1 mol / L oxalic acid ethanol solution, heated and stirred at 60°C in an oil bath, filtered and washed after the reaction is complete, and then the layered oxide powder NaNi after the treatment is carried out in step (4) 0.5 Co 0.2 Mn 0.3 O2 and disodium dihydrogen pyrophosphate according to the molar ratio of NaNi 0.5 Mn 0.5 O2:P2O7 4- =1:0.03 weighed and mixed evenly in ethanol, heated and stirred at 90°C in an oil bath, filtered, washed and dried after the reaction was complete, sintered at 500°C in an air atmosphere in a muffle furnace for 6h, sieved after cooling, and obtained the positive electrode material 0.01 (Na4P2O7@NaNi 0.5 Mn 0.5 O2.
[0148] Application and performance testing
[0149] The sodium ion battery positive electrode materials prepared in the above examples and comparative examples are respectively used to construct sodium ion button batteries, and the specific operations are as follows:
[0150] Positive electrode sheet: Grind the positive electrode material, conductive carbon black and PVDF binder in a mass ratio of 8:1:1, add appropriate amount of NMP to make slurry, evenly apply it on the pretreated aluminum foil, roll it after drying, and cut it into 14mm round positive electrode sheets;
[0151] Negative electrode: Sodium metal sheet with a diameter of 14 mm and a thickness of 0.2 mm;
[0152] Diaphragm: Whatman GF / F glass fiber with a diameter of 16 mm;
[0153] Electrolyte: electrolyte is 1 mol / L NaPF6, solvent is DC and DEC (volume ratio is 1:1), 5% FEC additive;
[0154] The positive electrode sheet, separator, negative electrode sheet and electrolyte are assembled in a glove box filled with high-purity argon to obtain a CR2032 button battery.
[0155] The electrochemical performance of the CR2032 button cells constructed with different sodium-ion battery cathode materials was tested using the Blue Power Battery Test System:
[0156] Charge specific capacity and discharge specific capacity test: charge to 4.0V at a current density of 13mA / g, record the charge specific capacity, then discharge to 2.0V at a current density of 13mA / g, record the discharge specific capacity, and calculate the coulombic efficiency = (discharge specific capacity / charge specific capacity) × 100%;
[0157] Cycle performance test: After activation by charging and discharging for 2 cycles at a current density of 13 mA / g, charge to 4.0 V at a current density of 130 mA / g, and then discharge to 2.0 V at a current density of 130 mA / g, record the first discharge specific capacity, cycle charge and discharge for 50 cycles, record the discharge specific capacity at the 50th cycle, and calculate the 50-cycle capacity retention rate = (discharge specific capacity at the 50th cycle / first discharge specific capacity) × 100%.
[0158] The test results are shown in Table 1 below:
[0159] Table 1
[0160]
[0161] It can be seen from Example 1 and Comparative Examples 1 and 2 and Example 6 and Comparative Examples 4 and 5 that the gradient setting of different element contents in layered oxides of different nickel-containing systems (Example 1 VS Comparative Example 1, Example 6 VS Comparative Example 4) is beneficial to improving the capacity, coulombic efficiency and cycle stability of the sodium ion battery; and the coating layer formed by the reaction of the inorganic acid radical ion source with the residual sodium and impurity oxides on the surface of the layered oxide (Example 1 VS Comparative Example 2, Example 6 VS Comparative Example 5) can effectively improve the coulombic efficiency, rate performance and cycle stability of the battery. It can be seen that the coating layer formed by treating the residual sodium and impurity oxides with an inorganic acid radical ion source is more conducive to promoting sodium ion diffusion and improving the battery capacity and structural stability than the pure NASICON electrolyte directly constructed on the surface of the layered oxide.
[0162] In addition, different from Example 1, Comparative Example 3 directly introduces an inorganic acid ion source and a metal salt to construct a solid electrolyte coating layer on the surface of the layered oxide. The capacity, coulomb efficiency, rate performance and capacity retention rate of the sodium ion battery constructed by the positive electrode material prepared by this method are inferior to those of the sodium ion battery constructed by the positive electrode material prepared in Example 1. It is speculated that this is because the impurity oxides remaining on the surface of the layered oxide are not charged and consumed, but instead increase the impedance of the positive electrode material and reduce the capacity of the battery.
[0163] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A sodium ion battery positive electrode material, characterized in that: It comprises a layered oxide and a solid electrolyte layer coated on the surface of the layered oxide; The chemical formula of the layered oxide is Na n Ni x M y O2, the Ni content of the layered oxide gradually decreases from the core to the surface, and the M content gradually increases; The solid electrolyte layer comprises one or more of sodium phosphate, sodium silicate and sodium pyrophosphate, and the solid electrolyte layer comprises at least one element of the M element; Wherein, M is selected from one or more of Ti, Co, Mn, Zn, Fe, Al and Cu; 0.8≤n≤1.1, 0.4≤x≤0.75, x+y=1.
2. A sodium ion battery positive electrode material according to claim 1, characterized in that: The molar ratio of the layered oxide to the solid electrolyte in the solid electrolyte layer is 1:(0.01-0.1); The layered oxide Na n Ni x M y O2 is also doped with element A, and the element A is selected from one or more of Mo, W, Sb, Nb, Sn, Ca, Sr, Li, Y, V, Cr, La, Ti, Co, Mn, Mg, Zn, Fe, Al and Cu, and the element A and the element M are selected from different elements; the doping amount of element A in the layered oxide is not higher than 0.
1.
3. A method for preparing a positive electrode material for a sodium ion battery, characterized in that: The following steps are involved: S1: providing a mixed solution A and a mixed solution B, wherein the mixed solution A and the mixed solution B are obtained by dissolving a Ni source and an M source in water; wherein, The concentration of the Ni source in the mixed solution A is greater than the concentration of the Ni source in the mixed solution B; The concentration of the M source in the mixed solution A is less than the concentration of the M source in the mixed solution B; The metal element M in the M source is selected from one or more of Ti, Co, Mn, Mg, Zn, Fe, Al and Cu; S2: continuously pumping the mixed solution B in S1 into the container containing the mixed solution A to form a precursor solution, and at the same time continuously pumping the precursor solution into a continuously stirred reaction container, and adding a precipitant and a complexing agent to react to obtain a precursor salt; S3: uniformly mixing the precursor salt prepared in S2 with a sodium source, performing a first calcination treatment to obtain a layered oxide, heating and stirring the layered oxide and an inorganic acid radical ion source in the presence of a dispersant, separating and collecting the solid, performing a second calcination treatment, and obtaining the sodium ion battery positive electrode material; or, The precursor salt prepared in S2 is heated and stirred with a sodium source and an inorganic acid radical ion source in the presence of a dispersant, and the solid is separated and collected for pre-calcination treatment, and then sintering treatment is performed to obtain the sodium ion battery positive electrode material.
4. The preparation method according to claim 3, characterized in that: In S1: The ratio of the total molar concentration of metal elements in the mixed solution A to the total molar concentration of metal elements in the mixed solution B is 1:(0.65-1.05); preferably, the total molar concentration of metal elements in the mixed solution A is 1-10 mol / L; The molar ratio of Ni element to M element in the mixed solution A is 1:(0.02-1), and the molar ratio of Ni element to M element in the mixed solution B is 1:(1.3-5); preferably, the Ni source is selected from one or more of nickel carbonate, nickel sulfate, nickel acetate, nickel chloride, nickel nitrate and nickel phosphate; the M source is selected from one or more of carbonate, sulfate, acetate, chloride, nitrate and phosphate.
5. The preparation method according to claim 3 or 4, characterized in that: In S1: The mixed solution A and the mixed solution B further comprise an A source; The A element in the A source is selected from one or more of Mo, W, Sb, Nb, Sn, Ca, Sr, Li, Y, V, Cr, La, Ti, Co, Mn, Mg, Zn, Fe, Al and Cu; The molar ratio of Ni element to A element in the mixed solution A is 1:(0-0.4), and the molar ratio of Ni element to A element in the mixed solution B is 1:(0-0.65); The concentration of element A in the mixed solution A is greater than or equal to the concentration of element A in the mixed solution B.
6. The preparation method according to claim 3, characterized in that: S2 includes at least one of the following features: (1) The precipitant is selected from one or more of NaOH, NaHCO3, and Na2CO3; (2) The complexing agent is NH3·H2O; (3) The continuous stirring rate is 500-1000 rpm; (4) The pH of the reaction is 9-12, the reaction temperature is 50-90° C., and the reaction time is 12-24 h; preferably, the reaction is carried out under a protective atmosphere.
7. The preparation method according to claim 3, characterized in that: S3 includes at least one of the following features: (1) The ratio of the total molar amount of metal elements in the precursor salt to the molar amount of sodium element in the sodium source is 1:(1-1.1); preferably, the sodium source is selected from one or more of sodium carbonate, sodium acetate, sodium oxalate, and sodium nitrate; (2) The molar ratio of the layered oxide to the inorganic acid ions in the inorganic acid ion source is 1:(0.01-0.1); preferably, the inorganic acid ion source is selected from one or more of a phosphoric acid source, a silicate source and a pyrophosphate source; the phosphoric acid source is selected from one or more of phosphoric acid, sodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, aluminum phosphate, zirconium phosphate, zirconium hydrogen phosphate, magnesium phosphate, yttrium phosphate, ammonium phosphate, ammonium dihydrogen phosphate, and magnesium ammonium phosphate; the silicate source is selected from one or more of silicic acid, sodium silicate, sodium metasilicate, sodium orthosilicate, and potassium silicate; the pyrophosphate source is selected from one or more of pyrophosphoric acid, sodium pyrophosphate, trisodium monohydrogen pyrophosphate, disodium dihydrogen pyrophosphate, and potassium pyrophosphate; (3) The dispersant is selected from one or more of ethanol, propanol, and N-methylpyrrolidone; (4) The temperature of the first calcination treatment is 700-1000° C., and the time of the first calcination treatment is 10-20 hours; preferably, the first calcination treatment is carried out in the presence of oxygen; (5) The heating and stirring temperature is 50-90°C, the heating and stirring time is 3-6h, and the heating and stirring speed is 200-800rpm; (6) The temperature of the second calcination treatment is 400-700°C, and the time of the second calcination treatment is 5-10 hours.
8. The preparation method according to claim 3, characterized in that: In S3, the pre-sintering temperature is 400-700°C and the pre-sintering time is 3-6h; The sintering temperature is 700-1000° C., and the sintering time is 10-20 hours.
9. A positive electrode sheet, characterized in that: The invention comprises the sodium ion battery positive electrode material according to claim 1 or 2, or the sodium ion battery positive electrode material prepared by the preparation method according to any one of claims 3 to 8.
10. A sodium ion battery, characterized in that: Including the positive electrode sheet as described in claim 9.
Citation Information
Patent Citations
Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery
CN108565457A
High-nickel material coated with aluminum and lithium silicate on surface and doped with fluorine on surface layer and preparation method
CN108807931A
Ternary cathode material and preparation method thereof, lithium ion battery and electric vehicle
CN110863245A
Electrode material with manganese concentration gradient, preparation method thereof, and sodium ion battery
CN111224093A
Sodium ion positive electrode material, preparation method thereof and secondary battery
CN115939370A
Cited By
Preparation method and application of sodium ion battery composite positive electrode material
CN120483278A